Pengaruh Perputaran Piutang, Perputaran Persediaan, Perputaran Utang, Leverage dan Ukuran Perusahaan Terhadap Profitabilitas - Piranti, Endang; Hermanto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to examine the influence of various working capital elements, including accounts receivable turnover, inventory turnover, accounts payable turnover, leverage, and company size, on profitability. Using secondary data, this analysis utilizes the financial statements of companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) during the period of 2018-2023. The analysis is conducted using the Eviews statistical software with secondary data. The findings of this research reveal that accounts receivable turnover has a positive effect on profitability, while leverage has a negative effect, and company size also positively contributes to profitability. Conversely, inventory turnover and accounts payable turnover do not show a significant impact on profitability. This study aims to provide a deeper understanding of the various aspects influencing profitability, assist company management in making more effective decisions, and highlight the importance of financial statements in expanding managerial understanding of working capital management to ensure business continuity.